Gambling among older greek australians influence of illusion of control beliefs and risk taking - Ohtsuka, Keis; Karoglidis, Helen (The National Association for Gambling Studies, 2001)
This study explored (a) whether illusion of control beliefs and risk-taking predict problem gambling within the elderly Greek-Australian community, and (b) types of leisure activities associated with gambling. One hundred sixty-four elderly Greek Australians (67 males, 84 females, 13 unknown sex) completed questionnaires on demographic questions, a modified version of the South Oaks Gambling Screen (Lesieur & Blume, 1993), questions regarding illusion of control beliefs, risk-taking, and leisure activities. Backward multiple regression analysis found that illusion of control beliefs, risk-taking, and age together predict problem gambling (accounted for 23% of the variance). Factor analysis isolated 3 groups of leisure activities. Factor 1 comprised dances (.61), eating out (.59), talking on the telephone (.59), and gambling (.75). Factor 2 included a distinct group comprising going for walk (.76), reading/writing (.81), and artistic/craft hobby (.54). Factor 3 accounted for outdoor activities (.75), coffee shop (.56), and part-time work (.57). Based on risk-taking, sensation seeking, illusion of control beliefs, sex, and level of education, the discriminant analysis classified non-problem and problem gamblers with 84.3% accuracy. The results suggest that illusion of control beliefs and risk-taking propensity play a major role in the formation of problem gambling among the elderly Greek Australians.